Improved ionic conductivity in guar gum succinate–based polymer electrolyte membrane. (October 2018) - Azzahari, Ahmad Danial; Abdul Mutalib, Nur Fazilah; Rizwan, Muhammad; Naceur Abouloula, Cheyma; Selvanathan, Vidhya; Sonsudin, Faridah; Yahya, Rosiyah
Guar gum succinate (GGS) was chemically modified by reacting guar gum with succinic anhydride in the presence of 4-dimethylaminopyridine. Succination was confirmed by Fourier transform infrared (FTIR) spectroscopy with carbonyl bands at 1724 cm −1 and ester linkage at 1567 cm −1 of the succinate group. The resulting amorphous, GGS was used as a polymer host to prepare cost-effective solid polymer electrolyte (SPE) films via incorporating a blend of ethylene carbonate (EC), carboxymethyl cellulose (CMC), lithium triflate (LiTf) and lithium iodide (LiI). SPE system for GGS:EC (1.0:0.6) with 30 wt% LiTf showed highest conductivity of 6.29 × 10 −5 S cm −1 and GGS:CMC:EC (0.5:0.5:0.6) with 25 wt% LiI showed highest conductivity of 2.10 × 10 −4 S cm −1 . FTIR revealed multiple complexation sites for ion mobility indicating that GGS possesses high prospects as a conductive SPE.